2001
DOI: 10.1074/jbc.m102063200
|View full text |Cite
|
Sign up to set email alerts
|

ERKs Regulate Cyclic AMP-induced Steroid Synthesis through Transcription of the Steroidogenic Acute Regulatory (StAR) Gene

Abstract: Cyclic AMP-dependent expression of the steroidogenic acute regulatory (StAR) protein is thought to be the controlling step for steroid production, but the mechanisms through which external signals are translated into increased transcription of the StAR gene are unknown. We demonstrate that cyclic AMP-induced steroid synthesis is dependent upon the phosphorylation and activation of ERKs and that ERK activation results in enhanced phosphorylation of SF-1 and increased steroid production through increased transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
130
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(151 citation statements)
references
References 52 publications
14
130
0
Order By: Relevance
“…In contrast, the role of ERK2/1 in the activation of adrenal steroidogenesis by ACTH or forskolin is controversial. Thus, forskolin was found to increase StAR expression and steroidogenesis in Y1 mouse adrenocortical tumor cells and to activate ERK2/1 (21). In contrast, in bovine fasciculata and rat glomerulosa cells, ACTH treatment did not lead to p42/44 mitogen-activated protein kinase (ERK2/1) activation (40,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the role of ERK2/1 in the activation of adrenal steroidogenesis by ACTH or forskolin is controversial. Thus, forskolin was found to increase StAR expression and steroidogenesis in Y1 mouse adrenocortical tumor cells and to activate ERK2/1 (21). In contrast, in bovine fasciculata and rat glomerulosa cells, ACTH treatment did not lead to p42/44 mitogen-activated protein kinase (ERK2/1) activation (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SF-1 has also been shown to regulate the expression of genes encoding cytochrome P450 hydroxylases and to efficiently transactivate the StAR gene in transient transfection assays in various cell types (13,15,16,19). Although the extent of SF-1 involvement in the regulation of StAR gene expression may present species-and cell type-dependent differences (20), it appears that activation of the cAMP-signaling pathway leads to increased phosphorylation (21) and/or expression (22) of SF-1 protein.…”
mentioning
confidence: 99%
“…As stated previously, both positive and negative effects of ERK1/2 activation have been reported for cAMP-stimulated StAR expression and steroid production. In Y1 mouse adrenal cells PD098059 treatment decreased the forskolin-stimulated increase in StAR steady-state mRNA levels by ϳ50% (44). In primary cultures of rat granulosa the MEK-1 inhibitor U1026 inhibited follicle-stimulating hormonestimulated increase in StAR mRNA (48), while in a transformed cell line U1026 potentiated the stimulatory effects of follicle-stimulating hormone on StAR protein levels (47).…”
Section: Discussionmentioning
confidence: 99%
“…45 Of the mitogen-activated protein kinase (MAPK) signaling molecules, ERK1/2 have been implicated in the modulation of steroidogenesis in granulosa cells [45][46][47] and other steroidogenic cells. 48 Our results indicated that ABM-Bu-G inhibited ERK1/2 phosphorylation in rat granulosa cells. These results imply that ERK1/2 signalling might be involved in the inhibition of progesterone secretion caused by adlay bran extracts in rat granulosa cells.…”
Section: Downregulation Of Progesterone Biosynthesis By Abm S-m Hsia mentioning
confidence: 56%